La arquitectura del siglo XX - Champion, Roberto Andres (Buenos Aires : Espaci, 1980)
Antecedentes históricos 1750-1914 y arquitectura 1919-1939
Keywords: ARQUITECTURA MODERNA; SIGLO XIX; SIGLO XX; ARQUITECTURA; HISTORIA